A Systemic Approach to Multi‐agency Community Safety. (17th December 2013) - Taylor, Mark John; Higgins, Emma; Francis, Hulya
<x xml:space="preserve">Abstract</x> In this paper, we examine a multiparadigm systemic approach to multi‐agency community safety. A detailed case study was undertaken of a multi‐agency partnership involving a fire and rescue service, a local council, an NHS primary care trust and a police force in the North West region of the UK. The community safety project studied was funded by the UK Department of Communities and Local Government over an 18‐month period. The multiparadigm approach used was beneficial for understanding the nature of community safety and its application in actual practice. The project involved the development of a novel customer segmentation approach based upon combined fire risk, health risk, social care risk and crime risk to support identification of at‐risk social groups to enable more targeted and coordinated provision of preventative measures for community safety by the public sector agencies involved. Copyright © 2013 John Wiley & Sons, Ltd.